Millimeter-wave CMOS front-end components design - Huang, Nan (2016)
Ranging from 30 to 300 GHz, millimeter-waves are whipping up flames of interest for all sorts of uses. They take the pressure off the lower frequencies and expand wireless communications into the outer limits of radio technology; they provide atmosphere windows upon the extremely high frequencies and benefit the bolometer-arrays seeking for smaller dimensions. At one time, this part of the spectrum was essentially unused, simply because few if any electronic components could generate or receive the millimeter-waves. All that has changed in the past decade or so. Millimeter-waves now gradually become practical and affordable, thanks to the development of CMOS technologies. Once implemented in CMOS, blocks that handle the millimeter-waves fit in perfectly with the digital ones, making the chip readily available for massive production. Although such integration capacity could overcome the bottleneck of compatibility, the millimeter-wave block yet remains as a stumbling block. MOS transistor’s insufficient intrinsic gain and lossy substrate limit the circuit performance. Therefore, the W-band CMOS circuits strongly need some refinement work in order to undertake two important millimeter-wave applications. The first important application is for the 76-77 GHz automotive radar. The second is the passive imaging, which utilizes an atmosphere window centered at 94 GHz. The scope of this thesis focuses on the millimeter-wave receiver’s front-end design. Based on a 65-nm CMOS technology, the following refinement works further stretches the CMOS limits, aiming to fulfill its potential in aforesaid millimeter-wave applications. The first two concentrate on the millimeter-wave application for automotive radars. There are frequency bands opened for vehicle radars to use. One is centered at the millimeter-wave frequency range, i.e. 77 GHz, which is known as the long-range radar. Another is centered at 24 GHz, known as the short-range radar. In order to make the best possible use of those two bands, a dual-band 24/77 GHz CMOS low-noise amplifier (LNA) is designed. It is the first time that a 24- and a 77-GHz LNA are combined using a CMOS technology. The proposed topology of the dual-band LNA greatly saves the chip area and the LNA consumes very little dc power, which is particularly suitable for the electric vehicle to use. In order to improve the sensitivity and the angular resolution, the single channel receivers should be combined as an array. The conventional combining method uses specific power dividers operating in only one frequency band. Moreover, a conventional Wilkinson power divider occupies a large chip area. In order to address these issues, a dual-band Wilkinson power divider is presented in this thesis. The proposed divider consists of lumped elements instead of quarter-wavelength transmission lines, which has greatly reduced the chip size. Its performance is as effective as that of a single-band power divider. The second two works are dedicated to the millimeter-wave application for passive imaging. An LNA and a mixer are designed. By properly applying positive feedback, the noise figure of the proposed LNA is minimized at 5.1 dB, and the bandwidth is extended to 30 GHz. The proposed LNA achieves the lowest noise figure among all reported 65 nm CMOS LNAs. The proposed mixer is developed from subharmonic mixers. Down-conversion process is achieved by capturing the phase difference between two sine waves at every half cycle of the local oscillator. The significant advantage of the presented mixer is that it saves one’s great trouble in designing phase-shifters. Moreover, the mixer covers a wide frequency band. Its conversion gain is above 3.5 dB across the entire W-band. In turn, it can also be used in a 77-GHz automotive radar.